EFEK INSIVILITAS PELANGGAN, PENYELIA DAN KARYAWAN TERHADAP EXHAUSTION EMOSIONAL - Tiarapuspa Tiarapuspa; Gita Novia Riani (Jurnal Manajemen dan Pemasaran Jasa, 2018)
This research aims to analyze the workplace incivility that is caused by customer, supervisor, and coworker and how it effects their emotional exhaustion. The object of this sample is frontline employees of casual restaurants in Jakarta. To test the hypotheses, this study distributes 170 survey questionners.  Among these, 21 questionners were excluded because of incomplete responses. A total 149 survey questioners were analyzed by using the method of Structural Equation Model (SEM). The result shows that only coworker incivility significantly increases the frontline employees’ emotional exhaustion. Further research can take another sample from different service industry.